The Great Migration
DOI: 10.4337/9781781000724.00018
|View full text |Cite
|
Sign up to set email alerts
|

The Socio-economic and Health Status of Rural–Urban Migrants in Indonesia

Abstract: This paper seeks to answer whether or not rural-urban migrants "make it", i.e. whether or not they are able to, at least, achieve a socioeconomic and health status similar to that of their nonmigrant counterparts living in the same city. Using specifically collected data on ruralurban migration, this study finds that, after controlling for various characteristics, migrants' household incomes are significantly higher than those of nonmigrants. They also have a significantly lower probability to be absolutely po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Using the same dataset of Indonesia, Resosudarmo et al (2009a) found that the average household income of migrants is significantly higher than that of local residents. They are also less likely to be poor than the nonmigrants as measured by improvements in their socioeconomic status.…”
Section: Literature Reviewmentioning
confidence: 97%
See 2 more Smart Citations
“…Using the same dataset of Indonesia, Resosudarmo et al (2009a) found that the average household income of migrants is significantly higher than that of local residents. They are also less likely to be poor than the nonmigrants as measured by improvements in their socioeconomic status.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Using data in several low-and middle-income countries, Tacoli et al (2008) also showed that the proportion of migrants among the urban poor ranges from 7 percent in Nigeria (the lowest), to 43 percent in Bolivia (the highest). Meanwhile, Resosudarmo et al (2009a) found that more than 10 percent of the lifetime migrants in Indonesia are likely to be among poor households. Due to poverty conditions, many poor migrants in Indonesia are also found to be sources of urban problems, such as the proliferation of slum areas in many big cities (Effendi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals who cannot master the language are generally confined to work in the informal sector or to long-term unemployment or underemployment. This is a driving force in urbanization and temporary as well as permanent migration in the nation today (Resosudarmo et al, 2009). In Australia, it is not uncommon for individuals with low levels of formal education in Indonesia to have great difficulty mastering English, despite living among English speakers.…”
Section: The Indonesian Speaking Community In Melbournementioning
confidence: 99%
“…1 This is surprising given that the study of socioeconomic status is more than an abstract exercise: the subjective perception of socioeconomic status has been shown to shape subjective well-being (Di Tella, Haisken-De New and MacCulloch, 2010;Akay, Bargain and Zimmermann, 2012) and the state of health (Adler et al, 2000;Dalstra et al, 2005;Demakakos et al, 2008). In one of the few existing studies on welfare and status adjustments ex-post migration, Resosudarmo et al (2010) show that rural-tourban migration in most cases improves the socioeconomic status of internal migrants in Indonesia. While the majority of migrants claim that their economic conditions are worse than those of their new non-migrant neighbours, in fact, their absolute expenditure levels exceed that of non-migrants.…”
Section: Introductionmentioning
confidence: 99%